Dual sourcing for mitigating humanitarian supply chain disruptions. Issue 2 (7th October 2014) - Iakovou, Eleftherios; Vlachos, Dimitrios; Keramydas, Christos; Partsch, Daniel
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Proactive planning strategies for "slow-onset" disruptions that affect humanitarian supply chains (SC) developed to address chronic pressing societal problems, can have a significant impact on boosting the operational and financial performance of these chains. The purpose of this paper is to develop a methodology that quantifies the impact of a risk mitigation strategy widely employed in commercial SCs, namely emergency sourcing (ES), on the performance of humanitarian SCs taking into account backorders' clearance time, unsatisfied demand, and cost. Design/methodology/approach – Discrete event simulation is employed in order to evaluate alternative ES strategies based on a total cost criterion, which incorporates inventory-related costs, as well as premium contract costs paid for emergency replenishment. Backorders' clearance time and time-to-recovery are also employed as a design parameters. Findings – The results document the significant impact of disruptions on expected total cost, and the beneficial role of ES in hedging against disruptions. To that end, the proposed methodology determines the optimal emergency contracted capacity for a given premium, or alternatively the maximum premium cost value that ensures the feasibility of the implemented ES strategy in the long-run, along with the associated cost and time savings, and reduction of the unsatisfied demand. Originality/value – The fundamental objective is to provide a decision-making support methodology for deciding on whether to implement an ES strategy or not in humanitarian SCs, and the level of the optimal contracted reserved capacity. The results could be of great value to aid providers, policy-makers, and regulators.